2014
DOI: 10.1002/jrs.4580
|View full text |Cite
|
Sign up to set email alerts
|

Raman spectroscopic investigations on transition‐metal dichalcogenides MX2 (M = Mo, W; X = S, Se) at high pressures and low temperature

Abstract: Transition-metal dichalcogenides have been investigated using Raman spectroscopy both being off-resonance and in resonance. The first-order Raman spectra of MoS 2 , MoSe 2 , WS 2 and WSe 2 single crystal synthesized by vapor transport technique have been studied as a function of hydrostatic pressure (0-20 GPa) and temperature (80-300 K). Isobaric and isothermal mode-Grüneisen parameters have been determined from the temperature and pressure-dependent Raman spectra. The pressure dependence of the chalcogen-chal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
64
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(73 citation statements)
references
References 52 publications
(122 reference statements)
9
64
0
Order By: Relevance
“…[34][35][36][37] The existence of the shear mode is due to the vibration of two adjacent rigid layers of MoSe 2 which confirmed the layered structure of as-grown MoSe 2 . [34][35][36][37] The existence of the shear mode is due to the vibration of two adjacent rigid layers of MoSe 2 which confirmed the layered structure of as-grown MoSe 2 .…”
mentioning
confidence: 53%
“…[34][35][36][37] The existence of the shear mode is due to the vibration of two adjacent rigid layers of MoSe 2 which confirmed the layered structure of as-grown MoSe 2 . [34][35][36][37] The existence of the shear mode is due to the vibration of two adjacent rigid layers of MoSe 2 which confirmed the layered structure of as-grown MoSe 2 .…”
mentioning
confidence: 53%
“…It is this sandwiched structure that endows MoS 2 with the important mechanical properties for solid lubricants 6,7 . The electronic, optical, and lattice dynamical properties have been under intense investigations 2,3,8 . The research on multilayers of MoS 2 , among many other multilayers of TMDs, has been fueled by their novel properties intrinsic to two-dimensional materials.…”
Section: Introductionmentioning
confidence: 99%
“…An early XRD study showed that the pristine 2 H c structure of WSe 2 was stable up to 35.8 GPa22. Later, a Raman investigation confirmed no structural anomaly up to 20 GPa23. Recently, a first-principles study revealed an anomaly at 40 GPa consistently in the bulk modulus, Young’s modulus and Poisson’s ratio of WSe 2 , which may imply a possible structural transition2124.…”
mentioning
confidence: 99%